Fatigue crack micromechanisms in a Cu-Zn-Al shape memory alloy with pseudo-elastic behavior (Fracture and Structural Integrity, 2015)
Shape memory property characterizes the behavior of many Ti based and Cu based alloys (SMAs).In Cu-Zn-Al SMAs, the original shape recovering is due to a bcc phase that is stable at high temperature. Afteran appropriate cooling process, this phase (?-phase or austenitic phase) transforms reversibly into a B2 structure (transition phase) and, after a further cooling process or a plastic deformation, it transforms into a DO3 phase (martensitic phase). In ?-Cu-Zn-Al SMAs, the martensitic transformation due to plastic deformation is not stable at room temperature: a high temperature “austenitization” process followed by a high speed cooling process allow to obtain a martensitic phase with a higher stability.In this work, a Cu-Zn-Al SMA in “as cast” conditions has been microstructurally and metallographicallycharacterized by means of X-Ray diffraction and Light Optical Microscope (LOM) observations. Fatigue crackpropagation resistance and damaging micromechanisms have been investigated corresponding to three different load ratios (R=0.10, 0.50 and 0.75).
Keywords: Zn-Cu-Al alloy